Monitoring System of the Road Embankment - Mikołaj Miśkiewicz; Błażej Meronk; Tadeusz Brzozowski; Krzysztof Wilde (The Baltic Journal of Road and Bridge Engineering)
The paper presents the analysis of the monitoring system of the embankment supported on concrete columns and overlaid by a load transfer platform with the embedded steel grid. This field investigation was to study the complex interaction between the columns, the load transfer platform layer, and steel grid via in situ measurements during erection and live loading of the embankment. The study was focused on the behaviour of steel grid and the behaviour of the outer rows of columns since there are limited reference data available for this problem. The system was designed to inform the engineers about the condition of the embankment at every stage of construction and during standard operation of the road. The measurements brought the information on strain variations of steel grid, concrete columns, and structural settlement and provided necessary evidence for the embankment numerical model validation.